Pumpkin day at the zoo - Meissner, Susan, 1961- (Tommy Nelson, an imprint of Thomas Nelson, 2023)
When families donate their used pumpkins and jack-o'-lanterns to the zoo, the animals chomp, chew, play, and give hearty hoorays for their favorite squishy squash.